2012
DOI: 10.1037/a0029327
|View full text |Cite
|
Sign up to set email alerts
|

Why does service with a smile make employees happy? A social interaction model.

Abstract: Drawing on the social interaction model, we examine the mediating role that the customer's display of positive emotions plays on the relationship between the employee's display of positive emotions and the employee's positive mood. We also examine the moderating role that the customer's personality traits-agreeableness, extraversion, and emotional stability-play on the relationship between the employee's display of positive emotions and the customer's display of positive emotions. The results show that the cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 67 publications
3
46
0
2
Order By: Relevance
“…In addition, the affective work event conceptualization aligns well with research documenting that employees and customers share similar emotions due to emotional contagion (Barger & Grandey, 2006;Elfenbein, 2014;Kim & Yoon, 2012;Tan, Der Foo, & Kwek, 2004), which can be thought of as the "tendency to automatically mimic and synchronize facial expressions, vocalizations, postures, and movements with those of another person and, consequently, to converge emotionally" (Hatfield, Cacioppo, & Rapson, 1994, p. 5). Recent conceptual work (Van Kleef, Homan, & Cheshin, 2012) also posits that emotions have interpersonal affective consequences, which in turn drive individuals' behavioral responses.…”
Section: Customer Mistreatment As An Affective Work Eventmentioning
confidence: 74%
“…In addition, the affective work event conceptualization aligns well with research documenting that employees and customers share similar emotions due to emotional contagion (Barger & Grandey, 2006;Elfenbein, 2014;Kim & Yoon, 2012;Tan, Der Foo, & Kwek, 2004), which can be thought of as the "tendency to automatically mimic and synchronize facial expressions, vocalizations, postures, and movements with those of another person and, consequently, to converge emotionally" (Hatfield, Cacioppo, & Rapson, 1994, p. 5). Recent conceptual work (Van Kleef, Homan, & Cheshin, 2012) also posits that emotions have interpersonal affective consequences, which in turn drive individuals' behavioral responses.…”
Section: Customer Mistreatment As An Affective Work Eventmentioning
confidence: 74%
“…Accordingly, the current findings suggest that our understanding of emotional labor's effects could benefit from applying the social interaction model of emotion regulation (Côté, ) and integrate the intrapersonal and interpersonal perspectives. The social interaction model has been used in recent research to demonstrate the affective links between employees and customers (e.g., Kim & Yoon, ), whereas the current research is among the first attempting to capture behavioral responses from customers to different emotional labor strategies. Although Kim and Yoon () found that service with a smile made employees happy, our findings suggest that this link might only exist when employees’ smile is authentic.…”
Section: Discussionmentioning
confidence: 99%
“…The social interaction model has been used in recent research to demonstrate the affective links between employees and customers (e.g., Kim & Yoon, ), whereas the current research is among the first attempting to capture behavioral responses from customers to different emotional labor strategies. Although Kim and Yoon () found that service with a smile made employees happy, our findings suggest that this link might only exist when employees’ smile is authentic. Instead, when employees display faked positive emotions through surface acting, they tend to experience negative reactions from customers and, subsequently, negative affect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive emotion displayed by service employees has been recognized to evoke positive emotions in customers which ultimately lead to positive response (Kim & Yoon, 2012;Wu & Shen, 2013). During service encounters, the display of positive emotion by an employee triggers positive feedback from the customer.…”
Section: Hypotheses Developmentmentioning
confidence: 98%